THE EFFECTS OF ROTOR POLE ARCS, TURN_ON ANGLE ON TORQUE CHARACTERISTIC AND TORQUE RIPPLE OF SWITCHED RELUCTANCE MOTOR - Lĩnh (Journal of Military Science and Technology, 2021)
Switched Reluctance Motors have inherent advantages such as simple structure with non winding construction in rotor side, with no permanent magnet in the rotor, and possible operation in high speed. The high torque production in switched reluctance motor comes from the tendency of the rotor poles to align with the excited stator poles. SRM can operate in the whole magnetic circuit saturation region, thus making the most of the ferromagnetic material’s capabilities, power density per mass of the SRM. However, because SRM construction with doubly salient poles and its non-linear magnetic characteristics, the problems of acoustic noise and torque ripple are more severe than these of other traditional motors. Reducing torque ripple and maximizing average torque are one of the important goals of designing the SRM. Rotor pole arc is a parameter has a great influence on the average torque and the turn_on angle phase current is a decisive factor in the torque generation process. In the paper, the author analyzes the influence of turn_on angle on torque characteristics, the relationship of stator/rotor pole arc with turn_on angle phase current. The finite element method, software Speed PC-SRD was employed to caculate and analysis with switched reluctance motors 6/4-30kW. The results are essential basis for the designing driver of switched reluctance motor.